Measurement of Fetal Mesencephalon and Pons Via Ultrasonographic Cross Sectional Imagining. (2nd January 2018) - Yang, Ruiqi; Li, Rui; Liu, Xuejuan; Fan, Limei; Zhang, Jialing; Wang, Libo; Teng, Hong
ABSTRACT: Objectives. This study evaluated the feasibility of measuring the fetal mesencephalon and pons by ultrasonographic cross sectional imaging to detect fetal central nervous system developmental abnormalities. Materials and Methods. Fetal ultrasonographic measurements included: Fetal mesencephalon anteroposterior diameters (MAD), mesencephalon transverse diameters (MTD), pons anteroposterior diameter (PAD) and proximal transverse diameters (PTD). Results. Nine-hundred ninety fetuses were imaged. Thirty-eight fetuses (observation group) presented central nervous system abnormalities; 952 fetuses without imaged abnormalities were utilized as the reference (control) group. Fetal MAD, MTD, PAD, and PTD in control fetuses showed a linear correlation with gestational age. Thirty-eight fetuses had 40 abnormal measurements (8 MAD, 8 MTD, 14 PAD, and 10 PTD), 16 in mesencephalon, and 24 in pons. All data fell below the 95% confidence intervals' lower limits for the corresponding gestational age. Conclusion. Using normative data based on 957 fetuses allows detection of size abnormalities of the pons and midbrain during fetal life.